Cambridge handbook of psychology, health and medicine - Llewellyn, Carrie (Cambridge : Cambridge University Press, 2019)
This third edition of the much acclaimed Cambridge Handbook of Psychology, Health and Medicine offers a fully up-to-date, comprehensive, accessible, one-stop resource for doctors, health care professionals, mental health care professionals (such as psychologists, counsellors, specialist nurses), academics, researchers, and students specializing in health across all these fields. The new streamlined structure of the book features brief section overviews summarising the state of the art of knowledge on the topic to make the information easier to find. The encyclopaedic aspects of the Handbook have been retained; all the entries, as well as the extensive references, have been updated. Retaining all the virtues of the original, this edition is expanded with a range of new topics, such as the effects of conflict and war on health and wellbeing, advancements in assisted reproduction technology, e-health interventions, patient-reported outcome measures, health behaviour change interventions, and implementing changes into health care practice.
Title from publisher's bibliographic system (viewed on 30 May 2019).
Keywords: Medicine and psychology -- Handbooks, manuals, etc